(untitled) (Research, Society and Development, 2022)
Neonothopanus gardneri (N. gardneri) is a species of bioluminescent fungus belonging to the order Agaricales (Marasmiaceae) found in South America. Its existence was first reported in 1840 by George Gardner in his travels to Brazil, where it is popularly called "coco flower". Found mainly in decaying leaves and in the trunk of dwarf palm trees called "pindoba" (Attalea oleifera) or babaçu (Orbignya phalerata), recently N. gardneri had some of its bioactives isolated and their respective structures elucidated. Thus, this paper aims to present and discuss the findings of the works produced involving this theme. Thus, for the development of this literature review, books and scientific articles were searched in the following databases: Scopus, PubMed, Science Direct, web of science, Royal Society of Chemistry (RSC) Publishing and Google Scholar (1990-2021). The following keywords were used to filter the productions: "Neonothopanus", "Neonothopanus gardneri", "Bioactivities", "Bioprospecting", "Secondary metabolite", "Endophytic" and "bioluminescence". Finally, it is possible to observe that studies involving this species of bioluminescent fungus have focused on explaining the mechanism of light production and its potential biological activities, among them, antitumor, antioxidant, antimicrobial and antileishmanial effects.